Implementation science: why should we care? - Chu, Frances (Journal of the Medical Library Association, 2024)
There is a 17-year gap between the publication of research which proves an intervention is efficacious and effective and the implementation of that same intervention into practice [1]. In behavioral health, only 14% of successful interventions are integrated into actual practice [2]. As such, Implementation Science is envisioned to address the research to practice gap. This research methodology becomes important as it looks to investigate how to get interventions to become embedded in practice and de-implement unproven or disproven interventions that may be harmful and/or ineffective for patients. The aim of this commentary is to raise awareness of health sciences librarians/information specialists about this research arena and encourage health sciences librarians to envision how they could be involved in implementation science projects and teams or even use implementation science in their practice.